The Jewish Unions in America Pages of History and Memories - Weinstein, Bernard (Open Book Publishers, 2018)
"Newly arrived in New York in 1882 from Tsarist Russia, the sixteen-year-old Bernard Weinstein discovered an America in which unionism, socialism, and anarchism were very much in the air. He found a home in the tenements of New York and for the next fifty years he devoted his life to the struggles of fellow Jewish workers. The Jewish Unions in America blends memoir and history to chronicle this time. It describes how Weinstein led countless strikes, held the unions together in the face of retaliation from the bosses, investigated sweatshops and factories with the aid of reformers, and faced down schisms by various factions, including Anarchists and Communists. He co-founded the United Hebrew Trades and wrote speeches, articles and books advancing the cause of the labor movement. From the pages of this book emerges a vivid picture of workers' organizations at the beginning of the twentieth century and a capitalist system that bred exploitation, poverty, and inequality. Although workers' rights have made great progress in the decades since, Weinstein's descriptions of workers with jobs pitted against those without, and American workers against workers abroad, still carry echoes today. The Jewish Unions in America is a testament to the struggles of working people a hundred years ago. But it is also a reminder that workers must still battle to live decent lives in the free market. For the first time, Maurice Wolfthal's readable translation makes Weinstein's Yiddish text available to English readers. It is essential reading for students and scholars of labor history, Jewish history, and the history of American immigration."